NEW METHOD FOR INVESTIGATING THE DENSITY-DEPENDENT DIFFUSION NAGUMO EQUATION - Akgul, Ali; Hashemi, Mir Sajjad; İnç, Mustafa; Baleanu, Dumitru; Khan, Hasib (Vinca Inst Nuclear Sci, 2018)
We apply reproducing kernel method to the density-dependent diffusion Nagumo equation. Powerful method has been applied by reproducing kernel functions. The approximations to the exact solution are obtained. In particular, series solutions are obtained. These solutions demonstrate the certainty of the method The results acquired in this work conceive many attracted behaviors that assure further work on the Nagumo equation.
Keywords: reproducing kernel functions; Nagumo equation